Pemilihan Baterai Kendaraan Listrik dengan Metoda Weighted Objective - I Made Indradjaja M. Brunner; Satria M. Brunner (Jurnal Serambi Engineering, 2021)
Transportation is a sector that contributes significantly to CO2 gas emissions and has the potential to continue to increase along with the addition of fossil fuel vehicles. Indonesia has plans to switch to electric vehicles as an alternative to reduce greenhouse gas (GHG) emissions from the transportation sector. The battery is an important component of an electric vehicle, and there are several alternative technologies that can be used. This paper  simulates the selection of a suitable battery from various type of batteries, including Lead-acid (PbA), Nickel Metal Hydride (NiMH) and Lithium-ion (Li-ion). The selection is made using the weighted objective method by presenting 5 criteria: energy density; emissions generated for battery production; energy factor of the manufacturing process; availability of critical raw materials required for cathodes and anodes; and availability of recycling facilities. Supporting data to determine the magnitude of each criterion is obtained from literature reviews. The analysis and comparison was carried out by giving weight to the assessment based on the data obtained. The results of calculations carried out in the paper show that the Lead-acid battery is a viable option for use at current time.However, if Indonesia already has NiMH and Li-ion battery recycling facilities, or is capable of producing Lithium-ion batteries, then the criteria and calculation factors can be added and improved.